Antioxidant activity of gadusol and occurrence in fish roes from Argentine Sea - Arbeloa, Ernesto Maximiliano (2010)
The occurrence of the natural antioxidant gadusol (3,5,6-trihydroxy-5-hydroxymethyl-2-methoxycyclohex-2-en-1-one) was quantified in fish roes of three species from Argentine Sea: argentine hake (Merluccius hubbsi), brazilian sandperch (Pinguipes brasilianus) and argentinian sandperch (Pseudopercis semifasciata). Significant yields of the compound were found in the sandperchs. The antioxidant activity of the isolated metabolite in aqueous solution was assessed by ORAC and ABTS assays and compared with that of other known natural antioxidants. The results indicate that gadusol is a good breaker of chain reactions carried by peroxyl radicals. Besides, its ability to reduce radicals is comparable to that of ascorbic acid. On this basis, fish roes from brazilian and argentinian sandpearchs are proposed as useful sources of antioxidants for human consumption. © 2009 Elsevier Ltd. All rights reserved.